NHS Activism: The Limits and Potentialities of a New Solidarity. Issue 3 (3rd April 2019) - Pushkar, Piyush
ABSTRACT: Using Thompson's conceptualization of the moral economy, I describe how NHS activists in the UK utilize moral arguments to form alliances between different occupational groups, in a political battle against health care privatization, reflecting how a consciousness is being built upon solidarity and shared interests. In this context, professional duties of health care professionals are linked to the interests of all citizens. I explore how the deployment of professional ethics elides a moral hierarchy that may hinder the movement's egalitarian potential. Abstract :